Implementasi Pengelolaan Aset dan Inventarisasi Barang di Lingkungan Sekretariat Daerah Kota Padang Panjang: Studi Pengalaman Magang - Deswita Aulia Utami (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This article examines the implementation of asset management and inventory of goods at the Regional Secretariat of Padang Panjang City, which is based on the author's internship experience. This research uses descriptive qualitative methods to provide an in-depth description of asset administration practices in the field. The main focus of this study is the implementation of asset administration through the Goods Inventory Card (KIB) as the foundation of recording, data collection of vehicles and laptops, and other asset documentation. The study also emphasizes the importance of the barcode system for efficiency and transparency, and highlights the role of regular maintenance in maintaining asset sustainability. The results show that inventory digitization, barcode labeling, and maintenance activities significantly improve the effectiveness of asset control and realize good governance. Nonetheless, challenges are still found in terms of real-time data updates and uneven readiness of human resources (HR). Overall, the findings provide valuable insights into the alignment between the theory and practice of asset management in the public sector.